2004
DOI: 10.1142/s0129183104006121
|View full text |Cite
|
Sign up to set email alerts
|

THERMODYNAMIC CALCULATION OF n-COMPONENT EUTECTIC MIXTURES

Abstract: This paper presents a simple numerical method to calculate the eutectic mixture composition and melting temperature. Using a Newton–Raphson method to solve the nonlinear problem, the calculation is possible for n-component eutectic. We tested this algorithm on inorganic and organic mixtures. A better correlation between experimental and numerical results has been found for organic compound

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…The decrease in the melting point of this eutectic relative to the melting point of LiCl (which is lower than T m of KCl) is 258°. Usually, a eutectic mixture is formed when a multicomponent system in a solid state forms a superlattice, which simultaneously releases all its components into a liquid mixture during a low‐temperature transition to a liquid state 33 …”
Section: Factors Affecting the Degree Of Reduction Of Actinoid Oxidesmentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease in the melting point of this eutectic relative to the melting point of LiCl (which is lower than T m of KCl) is 258°. Usually, a eutectic mixture is formed when a multicomponent system in a solid state forms a superlattice, which simultaneously releases all its components into a liquid mixture during a low‐temperature transition to a liquid state 33 …”
Section: Factors Affecting the Degree Of Reduction Of Actinoid Oxidesmentioning
confidence: 99%
“…Usually, a eutectic mixture is formed when a multicomponent system in a solid state forms a superlattice, which simultaneously releases all its components into a liquid mixture during a low-temperature transition to a liquid state. 33 The solubility of oxygen in the LiCl melt is about 11.6 mol%, but it decreases significantly with the addition of KCl or CsCl. It is shown that when AE metal chlorides are introduced into the melt, the behavior of the O 2 solubility turns out to be ambiguous: BaCl 2 somewhat reduces the solubility, while SrCl 2 increases it.…”
Section: Experimental Study Of the Uo 2 Reduction Mechanismmentioning
confidence: 99%
“…6c). Additionally, the eutectic point was estimated at X ED ¼ 0.3 and T ¼ À145 C by calculation based on a thermodynamic relationship between the composition and temperature: 24…”
Section: Eutectic Behavior Of Electrolytesmentioning
confidence: 99%
“…The most well-known thermodynamic model for predicting eutectic phase behavior is the simplest: the van't Hoff equation, also called the Schröder-van Laar equation. [10][11][12] The van't Hoff equation assumes ideal mixing, which means it does not take any excess mixing properties into account. Excess mixing properties are usually modeled via a regular solution model, 13,14 however, these are mainly applied for only binary mixtures.…”
Section: Introductionmentioning
confidence: 99%